Pengaruh Peran Konsultan Pajak Terhadap Penurunan Risiko Sanksi Perpajakan Di Kota Makassar - Sitti Rahma Nur Fadillah; Nugraha Abhull Azwad (Program Studi Administrasi Fiskal, 2025)
ABSTRACT This study aims to analyze the influence of tax consultants' roles on reducing the risk of tax sanctions in Makassar City. The research is motivated by the increasing cases of delays in tax reporting and payments, resulting in administrative sanctions, as well as taxpayers' limited understanding of tax regulations. This quantitative study employs a simple linear regression analysis technique. Data were collected through questionnaires and interviews involving 35 taxpayers and 5 tax consultants actively operating in Makassar. The findings reveal that the role of tax consultants has a significant impact on reducing the risk of tax sanctions, indicated by a standardized Beta coefficient of 0.813 and a significance level of 0.000 (< 0.05). This suggests that guidance, education, and consulting services provided by tax consultants can improve taxpayer compliance and reduce the likelihood of sanctions. However, external factors such as taxpayers' financial capacity also influence the effectiveness of the consultants' role. This study contributes to the enrichment of taxation literature and serves as a reference for tax authorities in designing strategies to improve compliance through collaboration with tax consultants. The results encourage taxpayers to actively utilize tax consultant services as part of an effective tax compliance strategy.